2009
DOI: 10.1007/s00404-009-1170-5
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum cardiomyopathy

Abstract: According to current definition, peripartum cardiomyopathy (PPCM) is a rare disorder in which left ventricular dysfunction and symptoms of heart failure occur in the last month of pregnancy. It has been reported that the incidence of PPCM is 1 in 3,000-4,000 live births. The pathogenesis is poorly understood, however, infectious, immunologic, and nutritional causes have been hypothesized. Clinical presentation includes usual signs and symptoms of heart failure, and unusual presentations such as thromboembolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 60 publications
2
66
0
6
Order By: Relevance
“…Persistent nocturnal dry cough, orthopnea and paroxysmal nocturnal dyspnea are frequently reported. 34 Other non-specific symptoms include dizziness, chest pain, abdominal discomfort and palpitations. Rarely, acute cyanosis, thromboembolic episodes and liver failure have also been reported.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Persistent nocturnal dry cough, orthopnea and paroxysmal nocturnal dyspnea are frequently reported. 34 Other non-specific symptoms include dizziness, chest pain, abdominal discomfort and palpitations. Rarely, acute cyanosis, thromboembolic episodes and liver failure have also been reported.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Aldosterone antagonists, both spironolactone and eplerenon, should be avoided during pregnancy because of the unknown interactions with hormonal pathways. On the other hand, less frequently used hydralazine and long-acting nitrates are valuable replacements for ACEIs and ARBs [13]. Finally, antithrombotic therapy should be considered in patients with seriously depressed LVEF, especially in the setting of atrial fibrillation.…”
Section: Stable Heart Failurementioning
confidence: 99%
“…On the basis of several reports series of PPCM, varying genetic pools and diverse environmental factors have been proposed as risk factors in different areas. Although not clearly delineated, there are several suggested risk factors for development and recurrence of PPCM (Bahloul et al, 2009;Demakis et al, 1971;Fett et al, 2005a;Fisher et al, 2008;Murali & Baldisseri, 2005;Moioli et al, 2010;Nkoua et al, 1991;Ntusi & Mayosi, 2009;Pearson et al, 2000;Sliwa 2006aSliwa , 2006b): -African race -appears to be the strongest risk factor, possibly due to a greater incidence of arterial hypertension in this group. Brar et al reported the incidence of PPCM in African-American women to be 2.9-fold higher than in whites, and 7-fold than in Hispanics (Brar et al, 2007).…”
Section: Epidemiologymentioning
confidence: 99%
“…The association with left ventricular dysfunction seems to be unique to pregnancy, as the same drugs do not determine similar complications in nonpregnant patients, even at high doses. -certain cultural practices performed during the puerperium which are frequently related with high incidence of PPCM, such as consuming lake salt or rock salt known as "kanwa" (to promote the flow of breast milk), or heating of the body on a clay bed with a fire beneath to keep warm (Moioli et al, 2010;Murali & Baldisseri, 2005); -socio-economic level is discussed as a risk factor, and can be summarized in a stereotyped profile: "poor African female, with malnutrition and multiparity, making strenuous and sustained physical effort during pregnancy" (Bahloul et al, 2009). …”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation